A Tool Chain for Model-based Development of Heat Pump Dryers. (2016) - Bockholt, Marcos; Katter, Michael; Pohl, Georg; Michael, Jan; Alpögger, Thomas
Abstract: This work describes a tool chain structured and synchronised in the actual development process of environment friendly heat pump tumble dryers for a sustainable model-based systems engineering. The challenge, the benefit and the success of a hardware- in-the-loop (HiL) test bench is presented as an example to demonstrate the sustainability of the tool chain.